ضوابط تحديد الإختصاص القضائي الدولي للمحاكم الوطنية لتسوية منازعات التلوث النفطي للبيئة هذا البحث هو جزء من رسالة الماجستير لم يتم نشرها - حسن, محمد جلال; کریم, تاران محمد (Sulaimani Journal for Humanities, 2022)
The international jurisdiction of the judiciary means a set of legal rules that determine the jurisdiction of national courts to adjudicate on disputes with a foreign element if submitted to them for adjudication. The rules of the international jurisdiction determine the scope of jurisdiction of national courts in considering disputes of an international nature. also depends on it if issued by a court competent to consider the litigation. If a dispute with a foreign element is brought before the judiciary, the judge, prior to initiating it, has to examine first whether that dispute falls within the jurisdiction of the courts of his country or not? The judge conducts this research in the light of the rules of conflict of international jurisdiction, and this is due to the absence of special rules regulating international jurisdiction I regards to civil accountability disputes, which requires that we refer to the general rules of amended civil code number 40 of the year 1952, and in some cases to code of implementation of judgments of foreign courts in Iraq number 30 of the year 1928. Thus, the possibility of adopting general disciplines in determining the international jurisdiction of the judiciary in civil liability and particularly negligence in general became clear and obvious to us. Since the Iraqi law did not overtly refer to the introduction of disciplines of the proper course of justice, what these disciplines realize, ensuring the rights of the litigants, the unity of the litigation and the prevention of conflicting judgments in one case, we suggested that the Iraqi law explicitly stipulates these disciplines.